Effects of major and trace elements from the El Kahfa ring complex on fish: Geological, physicochemical, and biological approaches - Saad, Eman; Hamed, Mohamed; Elshahawy, Abdelnaby M.; Abd El-Aal, Mohamed; Sayed, Alaa El-Din H. (Frontiers in Environmental Science, 2023)
The alkaline rocks are known with their enrichment of rare lithophilic elements including lithium, uranium and tin which may have negative impact on the aquatic life. Thus, this study offers an intensive investigation for the influencing of alkaline rocks on Nile tilapia (Oreochromis niloticus). The variation of blood profile, the induction of antioxidant enzymes, morphological erythrocyte, and histological structure have been carried out for the fish after 15 days of exposure to the alkaline rocks powder with dose of 100 µg/L. The result shows that there is a pronounced decrease in the blood profiles such as platelets and white blood cell counts. There is a failure in the liver and kidney functions. Moreover, it shows an increase in the activities of superoxide dismutase (SOD), and catalase (CAT) as antioxidant biomarkers. Also, the exposure to alkaline rocks induces the mutation of DNA and distortion in the erythrocytes. We can conclude that, the bulk alkaline rocks induced changes in hemato-biochemical and antioxidant parameters of the Nile tilapia. In addition, exposure to the bulk alkaline rocks compounds also caused poikilocytosis and nuclear abnormalities of RBCs which draws our attention to the seriousness of climatic changes and the occurrence of erosion or erosion of rocks and their access to water.